Hotspots of land use change in Europe - Tobias Kuemmerle; Christian Levers; Karlheinz Erb; Stephan Estel; Martin R Jepsen; Daniel Müller; Christoph Plutzar; Julia Stürck; Pieter J Verkerk; Peter H Verburg; Anette Reenberg (Environmental Research Letters, 2016)
Assessing changes in the extent and management intensity of land use is crucial to understanding land-system dynamics and their environmental and social outcomes. Yet, changes in the spatial patterns of land management intensity, and thus how they might relate to changes in the extent of land uses, remains unclear for many world regions. We compiled and analyzed high-resolution, spatially-explicit land-use change indicators capturing changes in both the extent and management intensity of cropland, grazing land, forests, and urban areas for all of Europe for the period 1990–2006. Based on these indicators, we identified hotspots of change and explored the spatial concordance of area versus intensity changes. We found a clear East–West divide with regard to agriculture, with stronger cropland declines and lower management intensity in the East compared to the West. Yet, these patterns were not uniform and diverging patterns of intensification in areas highly suitable for farming, and disintensification and cropland contraction in more marginal areas emerged. Despite the moderate overall rates of change, many regions in Europe fell into at least one land-use change hotspot during 1990–2006, often related to a spatial reorganization of land use (i.e., co-occurring area decline and intensification or co-occurring area increase and disintensification). Our analyses highlighted the diverse spatial patterns and heterogeneity of land-use changes in Europe, and the importance of jointly considering changes in the extent and management intensity of land use, as well as feedbacks among land-use sectors. Given this spatial differentiation of land-use change, and thus its environmental impacts, spatially-explicit assessments of land-use dynamics are important for context-specific, regionalized land-use policy making.
Keywords: 330; land use change; land systems; Europe; intensification; abandonment; spatial differentiation